Addressing Fascism: A New Politics of Experience? - Thaddeus D. Martin (Philosophies, 2024)
(1) Background: The rise of fascism in American and, indeed, throughout the world, prompts a question: why does fascism remain persistent in human existence? The question is one that Karl Jaspers might have asked regarding the origin and goal of history. The political description of fascism is not adequate to describe the lived experience of those drawn to it, and to assume such people to be irrational does not suffice. Rather, culture provides semiotic structure, which is phenomenologically embodied by people in a Mitwelt. (2) Results: Perhaps what is needed is not a political description of fascism but a communicological analysis that proceeds as a semiotic phenomenology of fascism as it is culturally embodied. Jaspers’ concept of evil frames fascism as colonialism turned against itself, disguised banally in such phenomena as Schadenfreude, as described by Lanigan. (3) I approach this question using a semiotic phenomenological method. (4) Conclusions: The fading colonial dominance in the form of cultural hegemony creates Laingian ontological insecurity and a desire for one’s inner fascist to identify itself in others. Addressing fascism requires new politics of experience.